Changing the perception of police culture: recognising masculinity diversity and difference in a "dirty hands" vocation. Issue 1 (10th January 2018) - Kennedy, Michael; Birch, Philip
Abstract : Purpose: The purpose of this paper is to problematise the application of hegemonic masculinity to police practice and culture. Design/methodology/approach: This paper offers a viewpoint and is a discussion paper critiquing the application of hegemonic masculinity to police officers, their practice and culture. Findings: The paper suggests that a broader conceptualisation of masculinity, offered by scholars such as Demetriou (2001), is required when considering policing and its culture, in order to more accurately reflect the activity and those involved in it. Research limitations/implications: Writings concerning police practice and culture, both in the media and academic discourse, are questionable due to the application of hegemonic masculinity. The application of hegemonic masculinity can create a biased perception of policing and police officers. Practical implications: The paper helps to engender a more accurate and balanced examination of the police, their culture and practice when writing about policing institutions and encourage social institutions such as academia to address bias in their examination of policing institutions and police officers. Originality/value: There has been limited consideration in regards to multiple masculinities, police practice and culture.